Answer:
[tex]x - y + 5 = 0[/tex]
Step-by-step explanation:
Given:
Required:
The equation of the line passing through two points is given by
[tex]\frac{y-y_{1} }{y_{2}- y_{1} } =\frac{x_{}- x_{1} }{x_{2} -x_{1} }[/tex]
So, [tex]\frac{y-3}{7-3} =\frac{x-(-2))}{2-(-2)}[/tex]
[tex]\frac{y-3}{4} =\frac{x+2}{2+2}[/tex]
[tex]\frac{y-3}{4} =\frac{x+2}{4}[/tex]
Now, [tex]y-3 = x+2[/tex]
On rearranging,
[tex]x - y + 3 + 2 = 0x - y + 5 = 0[/tex]
Therefore, the equation of the line is [tex]x - y + 5 = 0.[/tex]